2011
DOI: 10.4317/medoral.16.e459
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride concentration and pH of pediatric medicines regulary and long-term used by children

Abstract: Objectives: Our aim in this study was to determine the fluoride concentration and pH of 71 pediatric medicines regularly and long-term used by children. Study Design: The fluoride concentration was evaluated by selective electrode of fluoride (Orion). The pH was confronted using specific electrode (Orion) coupled to a potentiometer (Orion). The analyses were accomplished in duplicate. Pearson´s correlation and Kruskal-Wallis test were used. P-values below 5% were considered statistically significant. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Long-term use of medications is frequently associated only to the beneficial effects to children's general health, but it may have deleterious effects to the oral health if preventive measures are not incorporated after ingestion of liquid medications 24 . Considering the cariogenic and erosive potential of sweetened and acidic medications prescribed to children, it is important that health professionals, especially paediatricians and paediatric dentists, are engaged in educating parents to ensure adequate oral clearance after each dose of medication as a primary step for minimizing the risk of dental caries and erosion of dental structures related to long-term, and sometimes unsupervised, regimens with sugar-containing liquid oral medications 9 .…”
Section: Results Discussionmentioning
confidence: 99%
“…Long-term use of medications is frequently associated only to the beneficial effects to children's general health, but it may have deleterious effects to the oral health if preventive measures are not incorporated after ingestion of liquid medications 24 . Considering the cariogenic and erosive potential of sweetened and acidic medications prescribed to children, it is important that health professionals, especially paediatricians and paediatric dentists, are engaged in educating parents to ensure adequate oral clearance after each dose of medication as a primary step for minimizing the risk of dental caries and erosion of dental structures related to long-term, and sometimes unsupervised, regimens with sugar-containing liquid oral medications 9 .…”
Section: Results Discussionmentioning
confidence: 99%
“…Thus, this should be the contributing factor why group 1 showed greater sized craters in SEM compared with other PLM. Studies done by Kiran et al, 6 Cavalcanti et al, 7 Passos et al, 8 and Babu et al 4 had assessed pH in their respective studies and concluded that PLMs with critically low pH had the ability to initiate dental demineralization and can cause surface erosion by acting directly on enamel surface. At critical pH, enamel gets unsaturated and sufficiently high concentrations of unionized acid ensure the inward diffusion of enough acid to extend the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Levando em consideração que os antibióticos pediátricos líquidos representam um fator de risco à cárie dentária, é necessária uma certa cautela na prescrição desses fármacos. Além disso, é essencial uma adequada orientação quanto ao momento oportuno de administração do medicamento e a manutenção de uma satisfatória higienização oral 31,32 .…”
Section: Fonte: Autoresunclassified